2018
DOI: 10.1186/s12890-018-0648-y
|View full text |Cite
|
Sign up to set email alerts
|

Six underlying health conditions strongly influence mortality based on pneumonia severity in an ageing population of Japan: a prospective cohort study

Abstract: BackgroundMortality prediction of pneumonia by severity scores in patients with multiple underlying health conditions has not fully been investigated. This prospective cohort study is to identify mortality-associated underlying health conditions and to analyse their influence on severity-based pneumonia mortality prediction.MethodsAdult patients with community-acquired pneumonia or healthcare-associated pneumonia (HCAP) who visited four community hospitals between September 2011 and January 2013 were enrolled.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Emergency Medicine International conditions may strongly influence mortality based on pneumonia severity in aged populations [15]. A study by Zhang et al demonstrated that PSI performed better than CURB65 for mortality prediction, while its discriminative power decreased with advancing age [16].…”
Section: Discussionmentioning
confidence: 99%
“…Emergency Medicine International conditions may strongly influence mortality based on pneumonia severity in aged populations [15]. A study by Zhang et al demonstrated that PSI performed better than CURB65 for mortality prediction, while its discriminative power decreased with advancing age [16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PSI underestimate severity of young patients with CAP and was not advised to guide ICU admission, [17,18] and the underlying health conditions may strongly influence mortality based on severity in elderly patients. [19] Study by Zhang et al showed that PSI performed better than CURB65 for mortality prediction, while its discriminative power decreased with advancing age. [20] However, in our study, the predicting performance for 28-day mortality of PSI was similar to qSOFA and CURB65.…”
Section: Discussionmentioning
confidence: 99%
“…6,21 Several studies have reported the utility of serum albumin levels and BMI as prognostic factors for older patients with pneumonia. [23][24][25][26] Nevertheless, despite the ease of evaluating these indicators, they may be influenced by various factors.…”
Section: Discussionmentioning
confidence: 99%